2019
DOI: 10.4103/ijcm.ijcm_369_18
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of adolescent girls in tribal blocks of Maharashtra

Abstract: Context:Undernutrition among adolescents in tribal areas is an area of concern in India.Aims:This study aims to assess nutritional status of adolescent girls and to study their hygienic practices and awareness regarding adolescent programs.Settings and Design:Two blocks (Palghar and Dahanu) in Palghar district of Maharashtra.Subjects and Methods:The present study was a community-based cross-sectional study conducted among 240 unmarried adolescent girls in ten villages of the study area.Results:The mean age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…28 A study conducted in rural Gujarat by Trivedi et al in 2016 29 reported undernutrition was in nearly half of the sample (46.3%). Similarly, studies conducted in West Bengal, 30 Himachal Pradesh, 14 Maharashtra, 31 Assam 23 reported higher prevalence of underweight (49%, 33%, 55%, 49.4%). Some studies conducted in developing countries 24,26,27,34,35 also reported a higher prevalence of underweight among adolescent girls.…”
Section: Discussionmentioning
confidence: 83%
“…28 A study conducted in rural Gujarat by Trivedi et al in 2016 29 reported undernutrition was in nearly half of the sample (46.3%). Similarly, studies conducted in West Bengal, 30 Himachal Pradesh, 14 Maharashtra, 31 Assam 23 reported higher prevalence of underweight (49%, 33%, 55%, 49.4%). Some studies conducted in developing countries 24,26,27,34,35 also reported a higher prevalence of underweight among adolescent girls.…”
Section: Discussionmentioning
confidence: 83%
“…Logistic and regression analysis were performed to find the associations of risk factors. The mean Hb level was found to be 10.1 g/dL and 87% of the participants were anaemic [15]. Another cross-sectional study in the tribal areas of two blocks of Palghar districts of Maharashtra assessed the nutritional status, hygiene practices and awareness regarding adolescent programs.…”
Section: West Zonementioning
confidence: 99%
“…Several studies demonstrate widespread nutrient deficiency and undernutrition among adolescent girls in rural and tribal areas in India [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Rapid growth in adolescence requires increased nutrient intake monitoring and support to achieve full developmental potential [37].…”
Section: Introductionmentioning
confidence: 99%